Gambaran Persepsi Peserta Badan Penyelenggara Jaminan Sosial (BPJS) terhadap Efektivitas dan Peningkatan Layanan Mobile JKN di Kantor BPJS Kesehatan Cabang Jakarta Utara - Syakira Niyatazahra Al- Masudi; Ria Efkelin; Hardin Lamba (Universitas Muhammadiyah Manado, 2025)
The development of digital technology in public services has encouraged BPJS Health to innovate through the Mobile JKN application, aiming to facilitate public access to health services. This study aims to describe the perceptions of BPJS participants regarding the effectiveness and improvement of services through the Mobile JKN application, as well as to identify challenges in its implementation. A qualitative method with a case study approach was employed at the North Jakarta Branch Office of BPJS Health. Data were collected through in-depth interviews with BPJS participants who had used the Mobile JKN application. The findings indicate that while the application provides convenience in accessing services such as participant data checking, premium payments, and online queue registration, there are still several obstacles, including limited user understanding, technical issues, and lack of education from BPJS officers. Moreover, some features of the application are not fully optimized and still require participants to visit the BPJS office in person. The study concludes that the effectiveness of Mobile JKN in improving health services still needs enhancement in terms of technical performance, public outreach, and the quality of digital services to be more responsive and aligned with participants’ needs.